A Community Hospital NICU Developmental Care Partner Program: Feasibility and Association With Decreased Nurse Burnout Without Increased Infant Infection Rates. (August 2019) - Clubbs, Brooke Hildebrand; Barnette, Alan R.; Gray, Natallia; Weiner, Lauren; Bond, April; Harden, Jane; Pineda, Roberta
Abstract : Background: Volunteers can provide staff-directed sensory inputs to infants hospitalized in the NICU, but research on volunteer programs is limited. Purpose: To evaluate the feasibility of a developmental care partner (DCP) program in a level III NICU and determine its relationship with provider burnout and infant infection rates. Methods: DCPs were trained to provide sensory input to infants, based on the behavioral cues observed by the occupational therapists and nursing staff, in medically stable infants. Feasibility was assessed by documenting the process of training and utilizing volunteers, as well as tracking duration and frequency of DCP visits. Staff burnout measures were assessed using the Maslach Burnout Inventory Human Services Survey (MBI-HSS) before and after implementation. Infant infection rates before and after the introduction of volunteers were compared. Results: Seventy-two volunteers were interested, and 25 (35%) completed the DCP competencies and provided sensory exposures to 54 neonates, who were visited an average of 8 times (range 1-15). Twelve (48%) DCPs did once-per-week visits, and 9 (36%) did at least 50 contact hours. MBI-HSS scores for staff emotional exhaustion ( P < .001) and depersonalization ( P < .006) were lower after DCP implementation. There were no differences in infant infection rates before and after DCP implementation (Fisher exact P = 1.000). Implications for Practice: Volunteer-based DCP programs may be feasible to implement in community hospitals and could help reduce staff emotional exhaustion and depersonalization without increasing the incidence of infant infections. Implications for Research: Future research on NICU volunteer programs with larger sample sizes and different infant populations is warranted. Abstract : Supplemental Digital Content is Available in the Text.